2015
DOI: 10.1080/21553769.2015.1055862
|View full text |Cite
|
Sign up to set email alerts
|

Screening of cytotoxic and antimicrobial activity potential of AnatolianMacrovipera lebetina obtusa(Ophidia: Viperidae) crude venom

Abstract: The effects of snake venoms have been well known since ancient times. They contain a variety of biologically active proteins which have therapeutic potential. This study investigated the cytotoxic and antimicrobial activities of Anatolian Macrovipera lebetina obtusa venom against various cancer cells, Gram-negative and Gram-positive bacteria, and a fungal species. A549, HeLa, CaCo-2, U-87 MG and MCF-7 cancer cell lines and a normal cell line (Vero) were screened by the 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…Crude venom of M. l. obtusa showed dose-dependent cytotoxicity against some cancer cell lines, kidney epithelial cells from African green monkey (Vero), and human embriyonic kidney 293 cells (HEK-293) in previous studies (Samel, Trummal, Siigur, & Siigur, 2012;Ozen, İğci, Yalçin, Goçmen, & Nalbantsoy, 2015;Jahromi, Mirakabadi, & Kamalzadeh, 2016;Süzergöz et al 2016;Oghalaie, Kazemi-Lomedasht, Zareinejad, & Shahbazzadeh, 2017). Moreover, dose-dependent cytotoxic activity of M. l. lebetina venom against L929 mouse fibroblast cell line was also reported previously (Nalbantsoy et al, 2012).…”
Section: Discussionsupporting
confidence: 58%
“…Crude venom of M. l. obtusa showed dose-dependent cytotoxicity against some cancer cell lines, kidney epithelial cells from African green monkey (Vero), and human embriyonic kidney 293 cells (HEK-293) in previous studies (Samel, Trummal, Siigur, & Siigur, 2012;Ozen, İğci, Yalçin, Goçmen, & Nalbantsoy, 2015;Jahromi, Mirakabadi, & Kamalzadeh, 2016;Süzergöz et al 2016;Oghalaie, Kazemi-Lomedasht, Zareinejad, & Shahbazzadeh, 2017). Moreover, dose-dependent cytotoxic activity of M. l. lebetina venom against L929 mouse fibroblast cell line was also reported previously (Nalbantsoy et al, 2012).…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, it was suggested to use different methods in combination to assess cytotoxicity. 31 Selective cytotoxic effect of Anatolian M. lebetina obtusa against various cancer cell lines (not including leukemia) has been reported previously 26 and shown to be po- 26,30 Therefore, the cytotoxic potency of the venom on various cancer cell lines should be determined by an initial screening study. It has been reported that crude venom of M. lebetina (subspecies could be assigned as M. lebetina turanica, according the origin of the samples stated in the paper) inhibited the viability of K562 cells about 10% after treating with 50 µg/mL of venom for 72 h. 19 According to our results, M. l. obtusa venom was more potent on K562 cells, compared to M. l. turanica venom.…”
Section: Discussionmentioning
confidence: 99%
“…14,20,26,30,34 These studies resulted in the description of venom proteins possessing in vitro and/or in vivo anticancer activity, including disintegrin, metalloproteinase, CLP, PLA 2 , and LAAO. Anticancer properties of snake venom proteins and their therapeutic potential have been reviewed recently by various authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, metalloproteinase from Macrovipera lebetina transmediterranea venom was identified as a myotoxin causing muscle degeneration by affecting myofiber stability and disrupting interactions of myofibers with extracellular matrix components, such as laminin and fibronectin [ 68 ]. Macrovipera lebetina venom was also described as an extraordinarily valuable source of antibacterial, antifungal, and anti-neoplastic compounds [ 69 ]. Interestingly, the venom from different Macrovipera lebetina subspecies differ in their antiproliferative and antimicrobial efficiency against different cancer cell lines or bacterial and fungal species.…”
Section: Macrovipera Lebetinamentioning
confidence: 99%